Response of Capecitabine and Oxaliplatin Chemotherapy in Metastatic Colorectal Carcinoma - Asma Abdul Rashid; Amjad Zafar; Amina Jafar; Rabia Iqbal; Harris Siddiqi; Zaigam Ismail (Life and Science)
Objective: To evaluate the frequency of objective response of Capecitabine and Oxaliplatin (CAPOX) in patients with metastatic colorectal cancer. Study Design: A descriptive case study. Place and Duration of Study: The Study was conducted at the Oncology Department, Hameed Lateef Hospital Lahore, Pakistan from 17th July 2019 to 16th January 2020. Methods: A total of 80 participants aged 20-80 who were diagnosed with metastatic colorectal carcinoma were selected for the study. After baseline investigations and examination, all the patients were advised chemotherapy comprising oral capecitabine and oxaliplatin for 6 cycles. For assessment of the response, CT scans were done by the radiological department and reported after chemotherapy. Results: 3 (3.8%) showed complete response, 32 (40%) showed partial response, 26 (32.5%) showed no response, and 19 (23.8%) patients showed disease progression after six cycles of chemotherapy. (43.8%) patients had objective responses, and 45 (56.2%) patients showed no objective response. Conclusion: chemotherapy yields promising activity for treating metastatic colorectal cancer.